Breaking Bad News via Telemedicine: A New Challenge at Times of an Epidemic. (28th April 2020) - Wolf, Ido; Waissengrin, Barliz; Pelles, Sharon
Abstract : The COVID‐19 epidemic is transforming the most basic component of communication between patients and physicians: the face‐to‐face meeting. This commentary addresses the challenges unique to the oncologist conducting appointments via telemedicine.